Micropulse lidar measurements (Arctic Data Center, 2010)
This data set contains measurements from a Micropulse Lidar (MPL) system that is deployed at Summit Station, Greenland. This lidar points near-vertically and measures backscatter in two polarization states. The measured parameters are profiles of backscatter in the "parallel" channel and in the "depolarized" channel. Detailed information on these parameters and other aspects of the dataset are included in the netCDF header information for each file. The lidar is owned by the Department of Energy's Atmospheric Radiation Measurement (ARM) program, but has been loaned to ICECAPS to support this experiment. Field operations support is provided by the National Science Foundation's Arctic Observing Network (AON) Program.